Analisis Implementasi Aplikasi Pembelajaran Interaktif Calistung Dengan Pendekatan Technology Acceptance Model - Khairan AR; Ridwan Ridwan; Hidayatus Saidah (PTE FTK UIN Ar-Raniry, 2021)
The advancement of smartphone technology has an impact in the field of education, especially in application-based interactive learning media. Based on the results of interviews at the Paya Laba Public Elementary School (SDN), some of the students have difficulty in using interactive learning media based on applications, ranging from operating skills, equipment, habits, benefits and others. Thus, to measure the level of acceptance of the use of interactive learning applications for reading, writing and arithmetic skills at SDN Paya Laba culd conducted by using a theoretical method which described the level of technology acceptance, namely the Technology Acceptance Model (TAM). However, the study aims to analyze the implementation of interactive learning reading, writing, arithmetic based on android applications. The test was run by measuring the influence between variables in the TAM model, which labelling as Perceived Ease of Use, Perceived Usefulness, and Attitude towards Using Technology, Behavioral Intention to Use and Actual Technology Use. The data in this study were obtained from questionnaires which filled out by the respondents. The data analyzed with Structural Equation Modeling approach based on Partial Least Square (PLS-SEM) by using the SmartPLS application. The stages of data analysis started from designing the structural model, designing the measurement model, evaluating the measurement model, evaluating the structural model, and testing the hypothesis. From the research results based on the seven proposed hypotheses, there are six hypotheses declared accepted and one hypothesis rejected.